Renewable Energy Transition, Trade Openness, and CO2 Emissions Nexus in the Middle East - Maalel, Nabil (International Journal of Energy Economics and Policy, 2024)
Reducing pollutant emissions during the global energy transition from fossil fuels to renewables is a significant endeavor. Nonetheless, a significant portion of the Middle East (ME) economy continues to be based mostly on the extraction and use of fossil fuels, posing a threat to the environment in the area. Thus, the current study examined the impact of income growth, trade openness (TO), and the Renewable Energy Transition (RET) on CO2 emissions in 12 Middle East nations, from 2000 to 2019. The findings demonstrated that the ME area contains the Environmental Kuznets Curve (EKC). RET decreased emissions of CO2. Therefore, the transition to renewable energy reduced emissions in this ME region. On the other hand, TO enhances CO2 emissions. For the ME region, TO is concerned with the environment. The research recommends a quick RET to safeguard the environment from CO2 emissions.